Gambaran Penyimpangan Distribusi Obat Bebas Terbatas dan Obat Keras pada Toko Kelontong di RT 17 Wilayah “X” Kota Tarakan - Nursyafika Nursyafika; Irma Novrianti; Jufri Ubrusun (Journal Borneo, 2024)
Medicines are an important part of health services because it can help people overcome the disease they are experiencing. About Health regulates pharmaceutical companies that produce products called drugs. Drugs are distributed to licensed pharmaceutical facilities such as pharmacies and licensed drug stores. However, there are often distribution irregularities where drugs are found sold in non-pharmaceutical facilities such as grocery stores. This study aims to obtain an overview of the distribution of Limited Over-the-counter Drugs (OBT) and prescription medicine in Grocery Stores RT 17 area "X" Tarakan City. This study is a qualitative descriptive study using a sample of all grocery stores located in RT 17 region "X" who are willing to become respondents, namely as many as 21 stores. The results showed that most respondents sold limited over-the-counter drugs (OBT) and prescription medicine. A limited over-the-counter drug found in many grocery stores is Paramex sold in 9 stores. In addition to limited over-the-counter drugs, the region’s grocery stores also found prescription medicine such as amoxicillin, which were found in 10 stores. Based on the results of interviews and questionnaires of shop owners, it is known that the drugs are obtained through direct purchases from pharmacies and drug stores. It can be concluded that the RT 17 grocery store in area “X” of Tarakan City still sells Limited Over-the-counter Drugs and prescription medicine.